Implementation of Contextual Teaching and Learning Social Sciences Subjects to Increase Motivation and Learning Achievement - Ajeng Eka Prastuti; Sarmini Sarmini; Nugroho Hari Purnomo (The Indonesian Journal of Social Studies, 2020)
Contextual Learning Teaching and Learning as a learning concept that helps teachers link the material taught with real-world situations of students so that the knowledge possessed will be applied in the surrounding environment. The purpose of this study was to determine the planning, implementation and evaluation of learning Contextual Teaching and Learning social studies subjects to increase student motivation and learning achievement. The method used in this research is qualitative with qualitative descriptive research. The results showed that: the application of the Contextual Teaching and Learning learning model made students more active because the material taught was connected directly to the daily lives of students so students could more easily understand the material applied. Students are enthusiastic about the questions given by the teacher with different answers based on experience. Improved learning achievement because students understand not memorize.